High Flyers Developing the next generation of leaders - McCall, Morgan W. (Boston Harvard Business School Press, 1998)
This book challenges conventional wisdom about how to groom executives for the positions in your firm. It presents a strategic framework for identifying and developing future executives that senior managers can use to find the "hidden" talents in their midst. The key is to look for the people with the capabilities to run the business tomorrow-not today. McCall demonstrates that the best executives aren't necessarily managers who possess a previously indentified, generic list of traits or who have risen to the top through survival of the fittest. Rather, the real leaders of the future are those who have the ability to learn from their experiences and remain open to continous learning. If these people get the right experiences on the job, they will have the ultimate opportunity to learn new executive skills-and its the responsibility of the firm's current leadership, especially line management, to make that happen. Full of vivid real-life examples, High Flyers explains how senior managers can create an environment that supports the firm's business strategy with the kinds of experiences people need if they are to lead a company in fulfilling its mission. The book also shows how individuals can take charge of their own development and avoid common pitfalls that lead to falling off the excutive track.
Includes bibliographical references (p. 243-246)
Keywords: Executive ability